Influencing Mechanism of Detonator Location on Blasting Vibration with Electronic Initiation Technology - Junru Zhou; Dongwang Zhong; Lujun Cai; Liang Wu (Shock and Vibration)
Vibration velocity amplitude and frequency are the critical factors for assessing the adverse effects of blasting on surrounding structures. In this study, vibration signals were measured from a specially designed field test, in which blast holes were detonated by different initiation modes. Results of the field test indicate that the initiation mode has significant effects on blasting vibration. Then the influencing mechanism was revealed with the help of numerical simulation and theoretical analysis. Numerical simulation results show perfect accordance with filed test results. Five initiation modes to detonate the same explosion source, in descending orders of both velocity amplitude and vibration frequency, are the two initiation points, then the midpoint initiation and top and bottom initiation, followed by the bottom initiation and top initiation. By changing the location or increasing the number of detonators to reduce the length of subsource, the propagation path of detonation waves will be shrunk. Then the rising time of blast loading will be reduced and the rising rate will be accelerated, which lead to an increase in vibration frequency. In the meantime, the release and distribution of explosion energy will be accelerated unavoidably, which leads to an increase of vibration intensity. This study has considerable theoretical meaning and engineering value to guide for blasting construction.